A SYSTEMATIC REVIEW OF THE EFFECT IN USING RIDDLE GAME TECHNIQUE ON STUDENTS’ VOCABULARY MASTERY - Maria Peeva Mahseya Ngsurukh; Finny Anita; Elly Syahadati (XXXX-XXXX, 2021)
This research aimed to analyze the effect of the Riddle game technique on students’ vocabulary mastery can be an effective technique to increase students’ English vocabulary which is focused on synthesizing six previous studies (journals) about the Riddle game effect. The method of this research was using a systematic review. In this research, the sources consist of five journals and one proceeding conference paper. The sample of this research were six from eleven studies selected by inclusion and exclusion criteria using PRISMA Flow Diagram 2009. The data collection technique is library research or literature study through a search engine (Google Scholar) and  repositories from other universities. The tool to collect the data was the PRISMA protocol.  The data was analyzed by thematic analysis. The results of review showed that overall the students’ conditions of vocabulary mastery were changed into some advances, namely: (1) students’ score of English vocabulary was increased, (2) students’ language skill improved, (3) students’ intellection was developed, (4) students’emotional intelligence was increased. Therefore, students are more enthusiastic and enjoyed during vocabulary class. Shortly, these research sugessted to apply Riddle game in order to enhance students’ self confidence, critical thinking, and teamwork, which are needed for facing the competence in a world of job life.Keywords : Riddle Game, Systematic Review, and Vocabulary Mastery